On the impact of f(Q) gravity on the large scale structure. Issue 1 (31st March 2023) - Sokoliuk, Oleksii; Arora, Simran; Praharaj, Subhrat; Baransky, Alexander; Sahoo, P K
ABSTRACT: We investigate the exponential f ( Q ) symmetric teleparallel gravitation, namely f(Q)=Q+α Q_0(1-e^-β Q/Q_0) using ME-GADGET code to probe the structure formation with box sizes L Box = 10/100 Mpc h –1 and middle resolution N_p^1/3=512 . To reproduce viable cosmology within the aforementioned modified gravity theory, we first perform Markov Chain Monte Carlo (MCMC) sampling on OHD/BAO/Pantheon data sets and constrain a parameter space. Furthermore, we also derive theoretical values for deceleration parameter q ( z ), statefinder pair r, s and effective gravitational constant G eff, perform Om ( z ) diagnostics. While carrying out N -body+SPH simulations, we derive CDM+baryons over density/temperature/mean molecular weight fields, matter power spectrum (both 2/3D, with/without redshift space distortions), bispectrum, two-point correlation function and halo mass function. Results for small and big simulation box sizes are therefore properly compared, halo mass function is related to the Seth–Tormen theoretical prediction and matter power spectrum to the standard CAMB output.